Trachoma surveillance annual report, 2007: A report by the National Trachoma Surveillance and Reporting Unit - Tellis, Betty; Keeffe, Jill E; Taylor, Hugh R (Communicable Diseases Intelligence, 2008)
Trachoma screening was conducted in 2007 in trachoma-endemic regions and communities in the Northern Territory, South Australia and Western Australia. Aboriginal children aged 1 to 9 years were examined using the World Health Organization grading criteria. Screening in the Northern Territory was conducted by the primary health staff from the Healthy School Age Kids program, the Australian Government Emergency Intervention and Aboriginal Community Controlled Health Services with 60 of the 117 communities screened in 5 regions (1,703 children). In South Australia, the Eye Health and Chronic Disease Specialist Support Program and a team of eye specialists screened eight out of 91 communities in areas serviced by 5 Aboriginal Controlled Health Services (128 children). In Western Australia, population health unit and primary health care staff screened 62 out of 167 communities in 4 regions (1,666 children). Active trachoma prevalence rates varied between the regions with reported prevalence ranging from 5%–26% in the Northern Territory, 0%–21% in South Australia and 4%–22% in Western Australia. Comparisons of 2006 and 2007 regional active trachoma prevalence showed no consistent pattern in changes. Only a small amount of data were reported for the surgery and environmental improvement components of the World Health Organization recommended trachoma control activities of surgery (for trichiasis), antibiotic treatment (with azithromycin), facial cleanliness and environmental improvement. Reporting for the antibiotic treatment and facial cleanliness components has improved since 2006; however, many gaps still exist. A method to monitor bacterial resistance to azithromycin has been implemented. Baseline data collected by pathology services found similar results to national data collected by the Advisory Group on Antibiotic Resistance. Commun Dis Intell 2008;32:388–399.